Implementasi Etika Kepemimpinan dan Kepemimpinan Tranformasional Pada Kinerja Karyawan (Studi Literatur) - Rosita Pratiwi Junaidi; Fitria Agustina; Mohammad Abbas Sastrodiputro; Mochammad Isa Anshori (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Leadership is an important factor that determines employee performance and the organization's ability to adapt to environmental changes. The purpose of this study is to understand that ethics and transformational leadership greatly influence how employees work. This research is a research using literature study method or literature review. Through this qualitative approach, it is hoped that this research can provide in-depth insight into the Ethics and Transformation of a leader on the performance of employees. It was concluded from this study that the influence of ethics on employee performance has significant results related to ethical leadership and transformational leadership on employee performance to increase employee ability in ethics and employee courage because they get motivation from their leaders.